DESKRIPSI PENGAMBILAN KEPUTUSAN DALAM BERUSAHATANI PADI PANDAN WANGI (Oryza sativa L) DI KALANGAN PETANI (Studi Kasus pada Petani Lapisan Atas dan Lapisan Bawah Berdasarkan Luas Lahan di Desa Bunikasih Kecamatan Warungkondang Kabupaten Cianjur ) - Kundang Harisman Hadikusumah (JURNAL ISTEK, 2013)
This research aim to know the farmer base for in Pandan Wangi Paddy rice farming, farming acceptance and also its earnings. The analysis unit is rice field farmer Pandan Wangi Paddy at season plant 2012. Farmer of sample selected at random high rice modestly (Stratified Random Sampling) and size measure of sample farmer to eachevery strata used high rice random modestly with allocation of sample which is proportional (Proportionate Stratified Random Sampling). Matter which base on farmer in laboring paddy Screw pine Fragrant farming relate to situation of place and environment owning excellence, beside apropos of domicile economic aspect which concerning price, domiciling technical aspect which concerning domination of technique of Paddy farming Screw pine Fragrant and follow fomentation of PPL or government, and also pushed by farmer characteristic and family which concerning make-up of the quality of family life, availability of labor, and also follow will desire owner of farm. Evaluated from wide of the ownership of farm, of farmer of flake and also farmer of substratum, economic aspect represent dominant matter which base on farmer in laboring Paddy Screw pine Fragrant farming. Farmer of flake, situations of very compatible local nature represent the basis for strong also. however at farmer of substratum, domination of technique of farming represent the basis for strong also in laboring Paddy Screw pine fragrant farming. Acceptance of Paddy Screw pine fragrant concerning is ready of production facilities and basic facilities, production process, handling of result and also marketing. Availability of agriculture facilities and basic facilities obtained from capital alone and capital from outside. Input allocations in course of production have as according to fomentation, however in the case of manure and seed not yet as according to fomentation. Most farmers not yet used seed from result of purification and also usage of manure dose and type which not yet according to fomentation. Level of storey; level earnings of farmer of flake range from Rp 5.709.312 up to Rp 17.336.436. while farmer of substratum have earnings storey; level ranging from Rp 571.634 up to 6.771.342.